Como medir a confiabilidade de dobras cutâneas Measuring the reliability of skinfolds - Rosely Sichieri; Vânia de Mattos Fonseca; Claudia de Souza Lopes (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 1999)
Um dos métodos mais usados para a obtenção de informação relacionada à quantidade de gordura e sua distribuição no organismo é a medida de dobras cutâneas. O treinamento dos antropometristas para realização de medidas de dobras cutâneas representa um grande esforço na pesquisa nutricional e poucos estudos desenvolveram métodos práticos para a padronização destas medidas. O presente estudo compara os resultados de um estudo de confiabilidade utilizando os métodos previamente referidos e o coeficiente de correlação intra-classe (ICC), baseado no modelo ANOVA. Os resultados indicam que o ICC é o melhor método para a padronização dos antropometristas. One of the most widely used and inexpensive methods for obtaining information concerning the amount and distribution of human subcutaneous fat is the measurement of skinfolds. The skinfold measurement technique requires long-term supervised practice and repetition to obtain reliable results and there are few practical methods for standardizing measures taken by anthropometrists. Two studies, developed methodology to standardize skinfold measurements. We compared data of a reliability study, using the two methods previously discussed, with intraclass correlation coefficient calculations based on an ANOVA mixed model in order to assess two technicians measuring three skinfolds. The technicians tested were considered reliable only when using intraclass correlation coefficients. The intraclass correlation coefficient appears to be a better choice for the standardization of skinfold measurements, since it is not influenced by measurements with greater discrepancies such as those for obese individuals.